INVESTIGATION OF STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF DISCOVERY LEARNING METHOD IN READING COMPREHENSION - Ridha, Ahmad; Aminah, Aminah; Mukrim, Mukrim (Tadulako University, 2021)
The objectives of this research are to investigate and analyze the students’ perception on the implementation of Discovery Learning Method in reading comprehension and the challenges that the students face on the implementation of Discovery Learning Method in reading comprehension. In addition, this research was conducted through qualitative approach. The data of this research were taken from 30 students at SMK Negeri 1 Terpadu Sindue. In collecting the data of this research, the researcher used questionnaire and interview to the students. Questionnaire was used as the main instrument of this research and interview was used to support the results of the questionnaire. Questionnaire was in the form of statement and it included four degrees of answer option. Then, after analyzing the data obtained, it was concluded that Discovery Learning Method is effective to be implemented. It was perceived by the students that the method gives them insights of learning materials, allows them to explore the reading material, makes them more active in class, improves their analytical thinking, and gives them an opportunity to discover information collected earlier with friends. However, the students faced some challenges during the implementation of this method. The challenges that the students face on the implementation of Discovery Learning Method in reading comprehension are: the difficulty in understanding reading text which is too long, unclear instruction from the teacher, lack of vocabulary, and the learning situation (current teaching and learning process during the pandemic).